CuTe: Remarkable Bonding Features as a Consequence of a Charge Density Wave1. Issue 3 (23rd November 2012) - Stolze, Karoline; Isaeva, Anna; Nitsche, Fabian; Burkhardt, Ulrich; Lichte, Hannes; Wolf, Daniel; Doert, Thomas
<x xml:space="preserve">Abstract</x> CuTe bonds! A delicate balance between polyanionic TeTe bonds and multicenter CuCu and CuTe interactions is found in the modulated structure of CuTe. Modulated CuTe is thus an alliance of typical bonding properties of polyanionic and metal‐rich compounds.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>